Proceso de atención de enfermería en neonato pretermino con síndrome de dificultad respiratoria en el área de UCIN del Hospital General Guasmo Sur - Soria Gastesi, Jhommyra Izhamar (2020)
The nursing care process (PAE), is the application of the scientific method in nursing care practice, which allows to provide care in a rational, logical and orderly manner. The nursing care process consists of a 5-stage process: ASSESSMENT, DIAGNOSIS, PLANNING, EXECUTION AND EVALUATION, highlighting that nursing is a scientific discipline that focuses on the individual´s human response, which leads to a higher quality of care for the patient and satisfaction for the same. The SDR, previously called Hyaline Membrane Disease, is an acute respiratory condition that almost exclusively affects the Preterm Newborn (RNP) during the first hours of life, reaching its máximum intensity at 24-48 hours of life. The immaturity of the preterm Newborn lung is not only biochemical, pulmonary surfactant déficit, but also morphological and functional, since lung development has not yet been completed in these immature children. The lung with surfactant deficiency is unable to maintain adequate aeration and gas Exchange. The following clinical case is a Newborn of 34 SG, which passes through the área of Neonatal Intensive Care Unit acording to medical order, for presenting difficulty breathing, saturations of less tan 70%, presents cianosis in upper and lower limbs, pressure arterial 45/58 mmHg. Which enters the neonatal intensive care unit área to receive the corresponding care and treatment, through the nursing care process.